Криміналістична класифікація корисливо-насильницьких злочинів, що вчиняються неповнолітніми - Федосова, О. В.; Fedosova, O. V.; ORCID: http://orcid.org/0000-0002-5577-8333 (Юридична наука. - 2019. - № 7 (97). - С. 334-344, 2019)
Проаналізовано наукові підходи вчених щодо розкриття сутності, змісту і значення криміналістичної класифікації злочинів у системі криміналістичних знань, а також здійснено криміналістичну класифікацію корисливо-насильницьких злочинів, що вчиняються неповнолітніми. Запропоновано основними критеріями криміналістичної класифікації корисливо-насильницьких злочинів, що вчиняються неповнолітніми, вважати: особу неповнолітнього злочинця; обстановку вчинення злочину; предмет посягання; особу потерпілого; способи вчинення дій неповнолітніми з підготовки, здійснення і приховування корисливо-насильницького злочину; наслідки стосовно потерпілого; слідову картину злочину.

The relevance of the article is that in modern conditions of reforming the socioeconomic and political systems of society, integration into the European community and at the same time complicating the criminogenic situation due to the protracted economic crisis and declining living standards, unemployment, low solvency, creates a basis for committing crimes of selfish and violent orientation. An important role in improving the methodology of investigation of mercenary and violent crimes committed by minors belongs to the development of their classification. Forensic classification is an essential condition for the effective knowledge of mercenary and violent crimes committed by minors, the basis for the development of appropriate recommendations or their system. Scientific classification helps to reveal the essence of the studied objects, more fully and accurately identify and evaluate their properties, connections and relationships, contributes to the systematization of knowledge, conceptual apparatus, serves as a basis for further development of theories and positions in a particular scientific field. The essence and significance of forensic classification of crimes in the system of forensic knowledge are considered. The works of scientists on the problems of the theory of criminal classification of crimes in general and in relation to specific types of crimes in particular are analyzed. Criteria that are both criminally significant and common to a group of mercenary and violent crimes committed by minors are singled out as criteria for the forensic classification of crimes. It is offered to consider as the basic criteria of forensic classification of the mercenary and violent crimes committed by minors: the identity of a juvenile offender; the circumstances of the crime; subject of encroachment; the identity of the victim; ways of committing actions by minors to prepare, commit and conceal a mercenary and violent crime; consequences for the victim; trace picture of the crime. It is proved that the forensic classification of crimes committed by minors according to such criteria allows for a multifaceted analysis of selected categories of crimes, synthesize their forensically significant properties and provide appropriate forensic characteristics to such categories of crimes.

Проанализированы научные подходы ученых по раскрытию сущности, содержания и значения криминалистической классификации преступлений в системе криминалистических знаний, а также осуществлена ​​криминалистическая классификация корыстно-насильственных преступлений, совершаемых несовершеннолетними. Предложено основными критериями криминалистической классификации корыстно-насильственных преступлений, совершаемых несовершеннолетними, считать: личность несовершеннолетнего преступника; обстановку совершения преступления; предмет посягательства; личность потерпевшего; способы совершения действий несовершеннолетними по подготовке, совершению и сокрытию корыстно-насильственного преступления; последствия в отношении потерпевшего; следовую картину преступления.
Criminal classification of used and violent crimes committed by minors
Федосова, О. В. Криміналістична класифікація корисливо-насильницьких злочинів, що вчиняються неповнолітніми / Федосова О. В. // Юридична наука. - 2019. - № 7 (97). - С. 334-344.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; криміналістична класифікація; forensic classification; криминалистическая классификация; корисливо-насильницькі злочини; selfish and violent crimes; корыстно-насильственные преступления; неповнолітні; minors; несовершеннолетние